Hybrid rice adoption in Bangladesh: a socio-economic assessment of farmers' experiences - Husain, A.M. Muazzam; Hossain, Mahabub; Janaiah, Aldas (Research and Evaluation Division, Brac, 2019)
The study aimed at finding the farm-level adoption pattern, differential performances, relative profitability and constraints to adoption of two hybrid rice varieties viz., Alok 6201 and Sonar Bangia (CNSGC 6). These varieties were introduced during 1999 Boro season in Bangladesh. Findings show that farm size had a negative but education had a positive effect on adoption rate. Grain yield of hybrids were 15% higher than that of HYVs though Sonar Bangia did much better than Alok 6201. Input costs of hybrids were 23% higher. Profitability of Sonar Bangia was higher but that of Alok 6201 was lower than that of HYVs. Constraints to hybrid rice adoption included external dependence and higher seed cost, higher need for management skill, input intensity, higher incidence of pests and diseases, inadequate yield gain and lower head-rice recovery. Special constraints of A/ok 6201 include high rate of unfilled grain, grain shedding, crop lodging and poor keeping quality of cooked rice. Stickiness of cooked rice and relatively inferior quality in terrns of taste may also be considered as other constraints for boi.h varieties. Some of these problems would have been avoided if, instead of introducing rice hybrids without a clear deployment srategy, they were introduced to Bangladesh after scientific on-farm testing for 2-3 seasons/years across agro-ecological regions. Results tentatively imply that Alok 6201 may not be sustained for adoption. Though Sonar Bang/a was highly profitable, its inferior quality may also inhibit growth in its adoption in the long run. High quality local hybrids may be developed and domestic production of hybrid seeds may be expedited. Hybrids for rain-fed environment and resistant to biotic stresses may also be developed. Research infrastructure, scientific onfarm testing of new hybrids before releasing them, integration of credit with extension services, better management practices and co-ordination between public sector and NGOs/private sector should be strengthened.